Impact of ethical climate on moral distress revisited: Multidimensional view. (February 2015) - Atabay, Gülem; Çangarli, Burcu Güneri; Penbek, Şebnem
Background: Moral distress is a major problem in nursing profession. Researchers identified that the stronger the ethical basis of the organization, the less moral distress is reported. However, different ethical climates may have different impacts on moral distress. Moreover, conceptualization of moral distress and ethical climate as well as their relationship may change according to the cultural context. Objectives: The main aim of the study is to investigate the relationship between different types of ethical climate as described in Victor and Cullen's framework, and moral distress intensity among nurses in Turkish healthcare settings. Research design: An online survey was administrated to collect data. Questionnaires included moral distress and ethical climate scales in addition to demographic questions. Participants and research context: Data were collected from registered nurses in Turkey. In all, 201 of 279 nurses completed questionnaires, resulting in a response rate of 72%. Ethical considerations: Ethical approval was obtained from the university to which the authors were affiliated, after a detailed investigation of the content and data collection method. Findings: Factor analyses showed that moral distress had three dimensions, namely, organizational constraints, misinformed and over-treated patients, and lack of time and resources, while ethical climate had four types, namely, rules, well-being of stakeholders, individualism, and organizational interests. Positive correlations were identified between certain types of ethical climate (rules, individualism, or organizational interests) and moral distress intensity. Discussion: Factor distribution of the scales shows some commonalities with the findings of previous research. However, context-specific dimensions and types were also detected. No particular ethical climate type was found to have a negative correlation with moral distress. Conclusion: Recommendations were made for reducing the negative impact of ethical climate on moral distress. These include solving the nursing-shortage problem, increasing autonomy, and improving physical conditions.